A narrative study on community practice through ESD (Education for sustainable development): A case study of high school teacher community - Mihee Ryu; Byungjun Yi; Mikyung Jung; Leeyu Lee (Adult Education Research Conference, 2014)
The purpose of this study is to create 'ESD Community of Practice' through the 'ESD training experience' in school and to narrate the 'experience' and the 'story' of the teachers who are teaching ESD classes in school.